THE EFFECTIVENESS OF USING CROSSING FORMULAS OF TENSES TABLE IN LEARNING ENGLISH 16 TENSES AT XII GRADE STUDENTS OF MA MADANI ALAUDDIN PAOPAO IN ACADEMIC YEAR OF 2015/2016 - Abd. Gafur Hafid (Universitas Islam Negeri Alauddin Makassar, 2016)
The main objectives of this research were (1) To know whether the Crossing Formulas of Tenses Table is effective in Learning English 16 Tenses or not, (2) To find out how effective the Crossing Formulas of Tenses Table is in learning English 16 tenses. This research was conducted at MA Madani Alauddin Paopao in academic year of 2015/2016. The research design was Quasi Experimental Design with Pre-test and Post-test Design. The instrument used to collect the data was pre-test and post-test. The population of this research was XII Grade Students of MA Madani Alauddin Paopao which consists of class XII A and XII B. Class XII A had 26 students and class XII B had 24 students, therefore, the population of the research was 50 students. The technique used in sample taking was Cluster Random Sampling. Therefore, the sample of this research was 20 students in class XII A as experimental class, and 20 students in class XII B as controlled class. The result of pre-test showed that XII grade students’ ability about tenses was bad before the treatments were given. After giving treatment, the students’ mean score of post-test were increased significantly. To find out whether there was significance different between experimental class and controlled class, the researcher applied t- test. The result of t- test showed that the t-test value was higher than the t- table value at the level of significance was 0.05 with degree of freedom (df) (N1 + N2)-2 = (20 + 20)-2 = 38. It indicated that H1 was accepted and H0 was rejected. Based on the result of this research, it can be concluded that The Crossing Formulas of Tenses Table is effective in Learning English 16 Tenses at XII grade students of MA Madani Alauddin Paopao and there is significant difference between the students’ ability about English 16 tenses before and after using The Crossing Formula of Tenses Table.